2018
DOI: 10.1007/164_2018_158
|View full text |Cite
|
Sign up to set email alerts
|

Techniques and Applications of Magnetic Resonance Imaging for Studying Brown Adipose Tissue Morphometry and Function

Abstract: The present review reports on the current knowledge and recent findings in magnetic resonance imaging (MRI) and spectroscopy (MRS) of brown adipose tissue (BAT). The work summarizes the features and mechanisms that allow MRI to differentiate BAT from white adipose tissue (WAT) by making use of their distinct morphological appearance and the functional characteristics of BAT. MR is a versatile imaging modality with multiple contrast mechanisms as potential candidates in the study of BAT, targeting properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 100 publications
0
37
0
Order By: Relevance
“…In bone marrow, MR techniques have been emerging for measuring bone marrow water‐fat composition but techniques are lacking for the assessment of bone marrow adipose tissue (BMAT) microstructure, which is needed to differentiate between regulated BMAT and constitutive BMAT . In human adipose tissue depots containing brown adipose tissue, techniques assessing lipid droplet microstructure are needed to overcome the partial volume effects on the fat fraction measurements in regions containing both white and brown adipose tissue . The present results show that lipid droplet size measurements can be validated in water–fat phantoms and applied with good reproducibility in the tibial bone marrow.…”
Section: Discussionmentioning
confidence: 82%
“…In bone marrow, MR techniques have been emerging for measuring bone marrow water‐fat composition but techniques are lacking for the assessment of bone marrow adipose tissue (BMAT) microstructure, which is needed to differentiate between regulated BMAT and constitutive BMAT . In human adipose tissue depots containing brown adipose tissue, techniques assessing lipid droplet microstructure are needed to overcome the partial volume effects on the fat fraction measurements in regions containing both white and brown adipose tissue . The present results show that lipid droplet size measurements can be validated in water–fat phantoms and applied with good reproducibility in the tibial bone marrow.…”
Section: Discussionmentioning
confidence: 82%
“…Intensive research over the past years has changed the traditional view of adipose tissue from being an inert, lipid-storing depot to a highly dynamic, endocrine organ. The growing interest for a better understanding of brown adipose tissue (BAT) was triggered by the discovery of active BAT on 18 F-fluoro-2-deoxy-D-glucose ( 18 F-FDG) positron emission tomography (PET) scans in adult oncology patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…The high glucose consumption of activated BAT leads to a large number of studies, using 18 F-FDG PET as a surrogate marker for its metabolic activity [5][6][7]. Most of these studies, looking into the prevalence and factors that correlated with high BAT activity, were done on retrospective data and showed that active BAT was more commonly seen on 18 F-FDG PET scans in winter than in summer, in women than in man, and in normal weight vs obese patients [5,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MR-based techniques provide superior resolution, contrast, and quantitative information of BAT. 8,[28][29][30][31][32] The fat fraction (FF) imaging has been well established to investigate fat metabolism during activation of BAT in rodents [28][29][30]32 and clinical studies. [33][34][35][36][37] Dynamic contrast-enhanced (DCE)-MRI is sensitive for changes in tissue microvascular environment and physiological parameters of the tissue including the kinetics of blood flow.…”
Section: Introductionmentioning
confidence: 99%